2006
DOI: 10.1111/j.1365-2982.2006.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cortical potentials evoked by oesophageal balloon distention and acid perfusion in patients with functional heartburn

Abstract: Oesophageal visceral hypersensitivity is thought to be important in generating symptoms in functional heartburn (FH). However, the neurophysiological mechanisms involved are poorly understood. The aim of this study was to compare the characteristics of oesophageal cortical evoked potentials (CEPs) induced by balloon distension and acid perfusion in FH and controls. We studied 21 FH patients and 12 healthy volunteers. Oesophageal mechanical stimulation was performed using the specially constructed mechanical pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Of course, neural sensitization to heartburn in FH may lie more centrally. In patients with FH, it has been shown that dysfunction of visceral neural pathways and/or alterations in cortical processing may produce and mediate esophageal hypersensitivity . Moreover, mucosal acid exposure in FH subjects produces evoked cortical responses prior to inducing heartburn .…”
Section: Discussionmentioning
confidence: 99%
“…Of course, neural sensitization to heartburn in FH may lie more centrally. In patients with FH, it has been shown that dysfunction of visceral neural pathways and/or alterations in cortical processing may produce and mediate esophageal hypersensitivity . Moreover, mucosal acid exposure in FH subjects produces evoked cortical responses prior to inducing heartburn .…”
Section: Discussionmentioning
confidence: 99%
“…The first objective evidence to support the role of increased oesophageal afferent pathway sensitivity in a human model of oesophageal hyperalgaesia, came from a study which recorded OEP prior to and following a 30-min acid infusion. 31 In addition, in functional heartburn patients, Yang et al 32 described enhanced OEP to mechanical oesophageal stimulation in 21 patients when compared to healthy subjects. 9 These data have been replicated by a second group 19 and similar studies using functional magnetic resonance imaging have recently provided complementary evidence to support the notion that experimental oesophageal acidification can amplify central signalling of both innocuous and luminal inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical sensitivity to balloon distension is found in general to be normal60 or paradoxically reduced in patients with proven EO 63 64. This is in contrast to patients with functional heartburn/chest pain, in which baseline mechanosensitivity6567 and chemohypersensitivity68 69 have been demonstrated, and in which acid infusion leads to further increased sensitivity to subsequent electrical70 or mechanical stimulations 67 71. Hypersensitivity to heat (but not cold) has been demonstrated in patients with evident EO63 using a multimodal probe developed in Aalborg, Denmark.…”
Section: Experimental Studies In Humansmentioning
confidence: 95%